The relationship between high performance work system and safety performance among employees at workplace - Vanisa, A/ P Karupaiah. (Universiti Malaysia Sarawak (UNIMAS), 2010)
This study aims to study the relationship between high performance work system and employees' safety performance at workplace. Employees from Carsem (M) Sdn Bhd Ipoh, Perak made up the population for this study whereby 170 respondents participated in this study. A survey questionnaire which consisted four parts namely the demographic factors, overall safety performance at workplace, dimensions of high performance work system and open ended questions were constructed as a mean for data collection The variables included in this research are safety training, self-managed teams, information sharing, high-quality work and employment security. As for the relationship between the high performance work system and safety performance were determined by using inferential statistics which is the Pearson Correlation Analysis whereas the dominant factor was determined using the Simple Linear Regression Analysis. Besides that, this study has revealed that there are significant relationships between the dimensions of high performance work system and safety performance. The safety training were determined as the dominant factor that influences safety performance the most. New findings were discovered in this research which has strengthened the previous studies in this field. As a conclusion, several managerial implications and recommendations upon future research were also identified whereby it indicates that the high performance work system should be practiced at the workplace.